2020
DOI: 10.1186/s13690-020-00475-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction and its associated factors in South Gondar zone hospitals, Northwest Ethiopia, 2019

Abstract: Background After prematurity, intrauterine growth restriction (IUGR) is the second leading cause of perinatal mortality. IUGR has significant consequences in fetal, neonatal, and adult life. Currently, Ethiopia lacks information on IUGR’s prevalence and its determinants. This study aimed to assess the proportion of IUGR at birth and its associated factors. Methods A cross-sectional study was carried out among women who give birth in four hospitals of south Gonder zone from November 2018 to February 2019. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…The present study observed that participants who had IUGR were 2-fold increased odds of preterm birth. The finding is consistent with a cross-sectional study conducted in Ethiopia by Tesfa et al ( 18 ). The mechanism, which underpins this finding could be attributed to uteroplacental under perfusion that might have resulted in growth restriction of the fetus ( 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…The present study observed that participants who had IUGR were 2-fold increased odds of preterm birth. The finding is consistent with a cross-sectional study conducted in Ethiopia by Tesfa et al ( 18 ). The mechanism, which underpins this finding could be attributed to uteroplacental under perfusion that might have resulted in growth restriction of the fetus ( 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…This study was carried out among the four hospitals of the South Gondar zone (Debre Tabor, Nefas-Mewicha, Mekane Eyesus, and Addis Zemene). South Gondar is a zone in Ethiopian Amhara region [ 22 ]. In Ethiopia, even though there is a substantial increment in institutional delivery from 5% in 2005 to 48% in 2019, still greater than half (52%) of the women have delivered at home [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the quality of data, training was given for all data collectors at each hospital for one day on the overall procedure of data collection by the principal investigator and pediatricians supported with video [ 22 ]. The questionnaire was pretested before the actual data collection time on 5% of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Their dogma-establishing discovery, which they termed the Thrifty Phenotype Hypothesis, has been substantiated by thorough subsequent research that collectively estimates IUGR-born individuals to be at 18-fold greater risk for developing clinical metabolic disease by adulthood (reviewed in detail by Crispi et al, 2017 ; Yates et al, 2018 ). IUGR affects up to 25% of pregnancies worldwide and is the 2nd leading cause of perinatal mortality and morbidity ( Wu et al, 2006 ; Hoyert and Gregory, 2020 ; Tesfa et al, 2020 ). Moreover, the impact of IUGR on the health of surviving offspring can manifest as early as 3 years of age ( Iniguez et al, 2006 ; Milovanovic et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%